Developing Ethnomathematics-based E-Modules to Support Students’ Problem Solving Skills - Hamid, Jezlina; Rahmawati, Nur Indah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2024)
The lack of learning resources and learning media have an impact on reducing the quality of learning. Learning media innovation is needed to provide interactive and joyful learning and integrate cultural context. This research aims to create an ethnomathematics-based electronic module on the topic of number patterns based on ethnomathematics to support students' problem solving skills. This research uses 4D model (define, design, develop, and disseminate). This research involved 29 eighth-grade students from one of the junior high schools in Metro, Indonesia. The research results show that the ethnomathematics-based electronic module on number patterns topic meets the criteria for being suitable for use in learning based on experts review and is able to attract student interest. This fact indicates that ethnomathematics-based modules can be an innovative solution in improving the quality of mathematics learning in the digital era.